Usos e desusos de parques urbanos contemporâneos : estudo de caso Parque da Cidade-Serra/ES - Paula, Daniela de (2017)
Since the 1970s and 1980s, the emptying of public spaces and the emergence of new comfortable and safe leisure options have become usual in cities. On the other hand, recent researches show that popular actions associated with fisical interventions and pr